Plant diversity as a sustainable strategy for mitigating biotic and abiotic stresses in tomato cultivation - Cruz-López, Vianii; Granados-Echegoyen, Carlos Alejandro; Pérez-Pacheco, Rafael; Robles, Celerino; Álvarez-Lopeztello, Jonás; Morales, Isidro; Bastidas-Orrego, Lina María; García-Pérez, Florinda; Dorantes-Jiménez, Jaime; Landero-Valenzuela, Nadia (Frontiers in Sustainable Food Systems, 2024)
Sustainable agriculture has become a global priority in response to increasing food demand and the challenges confronting agricultural production, such as biotic and abiotic stresses. In this review, we delve into the role of plant diversity in mitigating these stressors within tomato cultivation. Our investigation reveals that the most extensively studied companion species are Vicia villosa Roth, Coriandrum sativum L., and Allium cepa L., while the primary stressors under scrutiny include nutrient deficiencies, aerial pests, and soil-borne pathogenic diseases. Regarding nutrient deficiencies, the cover crop system has demonstrated its capacity to provide essential nutrients directly and indirectly to plants. In addressing aerial pests and pathogens, all cultivation systems exhibit contributions. Finally, we assert that incorporating plant diversity into agroecosystems can effectively counteract various types of stressors. These benefits align with the application of agroecological principles and the development of sustainable agroecosystems. Further assessments of the effects of additional companion plant species are imperative. This should encompass the identification of their distribution, optimal plant quantities, and cultivation systems that enhance their benefits. Ultimately, these evaluations will aid in the formulation of comprehensive guidelines to facilitate the selection and utilization of plant diversity for long-term sustainability.